Changing and Correcting Gender and its Effect on Inheritance - Yassin , Hamid (Islamic Sciences Journal, 2023)
ABSTRACT Changing and correcting gender and its effect on inheritance: Praise be to God, Lord of the Worlds, and prayers be upon His Messenger and His Majesty Muhammad al-Hadi al-Amin. After the scientific development that we have reached in all fields, especially in the field of medicine, where man can change his gender from male to female and vice versa, and this change is according to the apparent meaning. If a person changes his gender, does he have all the rights of worship, dealings, marriage, rights and so on? I wanted to look into The issue of (changing and correcting sex and its effect on inheritance) in that it is worthy of the inheritance as it was or what it has turned into, with the distinction between sick and non-pathological cases. All of this I will answer it during this res.